2018
DOI: 10.3847/2041-8213/aaaa63
|View full text |Cite
|
Sign up to set email alerts
|

Are There Multiple Populations of Fast Radio Bursts?

Abstract: The repeating FRB 121102 (the "repeater") shows repetitive bursting activities and was localized in a host galaxy at z = 0.193. On the other hand, despite dozens of hours of telescope time spent on follow-up observations, no other FRBs have been observed to repeat. Yet, it has been speculated that the repeater is the prototype of FRBs, and that other FRBs should show similar repeating patterns. Using the published data, we compare the repeater with other FRBs in the observed time interval (∆t) -flux ratio (S i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 47 publications
2
78
0
Order By: Relevance
“…the arguments in favor of a magnetar engine are for some reasons unjustified); 2) Maybe some of the young magnetars formed the remnants are supramassive and have collapsed to black holes when our observations started; 3) The supernova ejecta may not yet become transparent to free-free emission at the observing frequency showed that the timescales for free-free transparency of the ejecta can vary from decades to up to a 100 years); 4) The synchrotron self-absorption by a flare-powered nebula may dominate the radiative processes; 5) FRB 121102 bursts are sporadic, and there are quiescent period (e.g. Price et al 2018); 6) FRB 121102 source is abnormally active compared with most young magnetars, as have been also suggested in previous studies (Palaniswamy et al 2018;Caleb et al 2019).…”
Section: Non-detection Probabilitysupporting
confidence: 59%
See 1 more Smart Citation
“…the arguments in favor of a magnetar engine are for some reasons unjustified); 2) Maybe some of the young magnetars formed the remnants are supramassive and have collapsed to black holes when our observations started; 3) The supernova ejecta may not yet become transparent to free-free emission at the observing frequency showed that the timescales for free-free transparency of the ejecta can vary from decades to up to a 100 years); 4) The synchrotron self-absorption by a flare-powered nebula may dominate the radiative processes; 5) FRB 121102 bursts are sporadic, and there are quiescent period (e.g. Price et al 2018); 6) FRB 121102 source is abnormally active compared with most young magnetars, as have been also suggested in previous studies (Palaniswamy et al 2018;Caleb et al 2019).…”
Section: Non-detection Probabilitysupporting
confidence: 59%
“…FRB 121102 was localized in a host galaxy with a redshift z = 0.19273(8) (Tendulkar et al 2017), confirming the cosmological origin of FRBs. Whether or not all FRBs are repeating sources is subject to debate (Palaniswamy et al 2018;Caleb et al 2019). In the literature, the FRB progenitor models can be grouped E-mail: sarah.spolaor@mail.wvu.edu † E-mail: kjlee@pku.edu.cn ‡ E-mail: zhang@physics.unlv.edu into two categories: the non-catastrophic models (related to repeating FRBs) such as giant magnetar flares (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We show how these likelihood functions can be used for parameter inference. This framework can help to infer the origin of FRBs as well as the origin of extragalactic magnetic fields (Caleb et al 2018;Palaniswamy et al 2018;Katz 2018).…”
Section: 2mentioning
confidence: 99%
“…Still, very little is known about the population and origin of FRBs (e. g. Katz 2018;Caleb et al 2018;Palaniswamy et al 2018;Caleb et al 2019;James 2019). To keep track of all the different models, they are collected in the living theory catalogue of FRBs (Platts et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…FRB 121102 is abnormally active, e.g. Palaniswamy et al 2018;Caleb et al 2019) or some interacting systems cannot produce FRBs because of their unfavorable pulsar parameters.…”
Section: Event Rate Densitymentioning
confidence: 99%